2013
DOI: 10.1016/j.neubiorev.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Foreign language training as cognitive therapy for age-related cognitive decline: A hypothesis for future research

Abstract: Over the next fifty years, the number of older adults is set to reach record levels. Protecting older adults from the age-related effects of cognitive decline is one of the greatest challenges of the next few decades as it places increasing pressure on families, health systems, and economies on a global scale. The disease-state of age-related cognitive decline—Alzheimer's disease and other dementias—hijacks our consciousness and intellectual autonomy. However, there is evidence that cognitively stimulating act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
148
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(151 citation statements)
references
References 194 publications
2
148
1
Order By: Relevance
“…It seems quite possible that, if these changes can be maintained to the elderly, they are bound to constitute cognitive reserve, suppressing the decrease of neurons or nerve fibers winding causing age-related cognitive decline. Given that the aged brain retains somewhat plasticity [40], foreign language learning initiated in old age is also likely to have analogous effects, and be used as an effective therapy to Alzheimer's disease [17]. However, up to present, few empirical studies have been conducted to give definite evidence to this end.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It seems quite possible that, if these changes can be maintained to the elderly, they are bound to constitute cognitive reserve, suppressing the decrease of neurons or nerve fibers winding causing age-related cognitive decline. Given that the aged brain retains somewhat plasticity [40], foreign language learning initiated in old age is also likely to have analogous effects, and be used as an effective therapy to Alzheimer's disease [17]. However, up to present, few empirical studies have been conducted to give definite evidence to this end.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is well accepted that typical manifestations may be memory loss and decline of executive control, poor working memory and slow information processing. Of course language and communication are also affected, including bad speech perception and production, reduced semantic comprehension in natural language environment, poor vocabulary memory, among others [17].…”
Section: Connotation and Categories Of Cognitive Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, cognitive benefits (Bak et al, 2016), neural reorganization (Mohr et al, 2014), and learning success (Marcotte and Ansaldo, 2014) have been demonstrated with language training in older adults. The literature on older adults' language learning remains sparse (Blumenfeld, 2012;Antoniou et al, 2013;Marcotte and Ansaldo, 2014;Bak et al, 2016) and clear practical and theoretical needs exist for a better understanding of language learning capacity across the lifespan. For example, of the US population above age 60, 15% speak a language other than English at home and, of these individuals, 58% speak English "less than very well" (Ryan, 2013).…”
mentioning
confidence: 99%